Effect Self Assessment System, Use of E-Filing, and Tax Collection on Taxpayer Compliance with Taxpayer Awareness as an Intervening Variable - Cahaya Adhitiya Natalie (Fakultas Bisnis, 2022)
This research is to examine the effect of self-assessment system, use of e-filing, and tax collection on taxpayer compliance with taxpayer awareness as an intervening variable. The population of this study is an individual taxpayer in Periuk Village. The Lemeshow formula that the researcher used and obtained a sample of 100 WPOPs. Accidental sampling (convenience sampling) became the chosen sampling technique. The data analysis technique used path analysis and the SPSS version 25 program. It was found that the variables of the use of e-filing, tax collection and taxpayer awareness partially did not affect taxpayer compliance, while the self-assessment system affected taxpayer compliance. And self-assessment system, use of e-filing, tax collection and awareness of taxpayers affect taxpayer compliance.